EXPLORING ETHICS AND AESTHETICS OF ECO-CARING IN UTTARARĀMACARITA - Dwivedi, Prabha Shankar (Journal of Dharma, 2021)
This article analyses and appreciates the skilful use of ethics and aesthetics as tools for prompting the care and concern in humans for non-humans and their surrounding environment in an eighth-century Sanskrit play Uttararāmacarita composed by Bhavabhūti. The play is a theatrical representation of the later phase of the theological narrative of Rāmāyaṇa with minor changes towards giving a happy ending to the Uttarakānda of Rāmāyaṇa. The playwright, having known the fact that Rāma and Sītā are immensely revered, deftly appeals to the ethos of the reader and audience for respecting the ecosystems. Bhavabhūti portrays Rāma and Sītā worshipping various phenomena of nature with a motive of creating equal reverence in the heart of people worshipping Rāma and Sītā towards nature so that a sustainable society could be created where nature remains revered and consequently unharmed. This paper shows the interdependence of social and ecological systems through the analysis of the play undertaken for study and claims that to achieve the sustainable development goals, the maintenance of healthy ecosystems is indispensable. This paper draws its contemporary relevance from its aim of exploring the ways of protecting environment to achieve various sustainable development goals set by the United Nations.